ANALISIS IMPLEMENTASI KEBIJAKAN PEMBERIAN AIR SUSU IBU EKSKLUSIF BAGI PEKERJA DI PT. APAC INTI CORPORA KABUPATEN SEMARANG - Agnes Melissa; Sutopo Patria Jati; Anneke Suparwati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
The scope of exclusive breastfeeding survey by Department of Health in dicated that in 2012, the mothers who breasfeed their children in District of Semarang were only as many as 34.6% lower than National Target (80%). PT. APAC employees consist of 4,081 worker women, with a total of 5% of the bore and only 4 % were breastfeeding. Policies has been made such as Statutes, but there are still many companies has not implement those policies.The objectives of this research was to find out the implementation of exclusive breastfeeding policy for workers during working hours in PT. APAC, the District of Semarang. The factors that affecting implementation policy are communications, resources, dispositions and bureaucratic structures.This research used qualitative method, and in-depth interview and observation for data collecting method. Respondents, or the subject of the research are Section Head of Health, Safety, Environment in PT APAC as prior informant, Section Head of Health Promotion in Department of Health the District of Semarang, Section Head of Manpower and Transmigration Department and breastfeeding working mother as triangulation respondent.The result of the research showed that the implementation of exclusive breastfeeding in PT. APAC in District of Semarang did not work well. This is due to the lack of internal regulations made by the company, as well as a chance to breastfeeding various factors affecting including: 1) Communication, lack of socialization from the company to all employees; 2) Availability of fund for implementing exclusive breastfeeding policy, because the lack of specific official individuals for breastfeeding such as breastfeeding counselor in the company; 3) Attitude and commitment of executor towards breastfeeding policy in PT APAC in District of Semarang, and coordination within Unit Supervisors; 4) Unavailable Standard Operating Procedure (SOP) and Operating Coordination with Unit Supervisors related to exclusive breastfeeding policy in the company.